The Effect of the Learning by Contracts Strategy on EFL Eleventh-Grade Students' Writing Performance in Jordan - Alqyyam, Younus Mahamoud; ALNatour, Amal Shehadeh (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to examine the impact of a contract learning strategy on the writing performance of eleventh-grade female students in Jordan who are learning English as a foreign language. Methods: The study adopted a quasi-experimental approach to examine the relationship between two variables as they exist in real-life settings, without manipulation by the researchers. The sample consisted of 84 students, divided into two groups: an experimental group of 42 students (who learned writing using the contract learning strategy through an educational program designed by the researchers) and a control group of 42 students (who learned writing using traditional methods as outlined in "Action Pack 11" textbooks). The results of the post-test on selected writing skills for the experimental group served as the dependent variable, while the contract learning strategy was the independent variable. Results: The results showed statistically significant differences at the level of (α = 0.05) in the writing performance of eleventh-grade students learning English as a foreign language in Jordan. These differences can be attributed to the teaching strategy (contract learning versus traditional strategies). Conclusions: The study revealed an improvement in the writing performance of participants following the implementation of the contract learning program. It recommends using the contract learning strategy to teach writing skills to students in Jordan, given its clear positive impact on the writing performance of the experimental group.